The Impact of the Executive Branch on US Foreign Policy in the Middle East between 2001 and 2021 - Arez Abdulqader Abdullah; Nawzad Abdullah Shukri (Zanco Journal of Human Sciences, 2026)
This study examines the role of the executive branch on the US foreign policy in the Middle East between 2001 and 2021. The executive branch has a decisive role in directing US foreign policy in the Middle East. The president has many responsibilities in US foreign policy. The most important duties of the president are commander-in-chief of the US military, head of US diplomacy, making agreements with states and appointing senior officials with the approval of the Senate. Alongside of the role the President of the United States, there are many other institutions which help president in term of implementing foreign policy. This includes, the State Department, the Department of Defense, the National Security Council and the Central Intelligence Agency (CIA). One of the goals of this study is to examine how the executive branch has influenced US foreign policy in the Middle East. Further, it is noticeable that the formulation and implementation of US foreign policy often depends on different worldviews and perspectives of presidents. In addition, presidents' policies and decisions evolve over time and vary depending on the subject matter. For example, in the relationship and treatment of US presidents with Iran, Turkey and Israel. Also, ancillary institutions have played a role in providing information, supporting policy, and implementing presidents’ policies.